REHABILITASI HUTAN DI KECAMATAN PERANAP OLEH DINAS KEHUTANAN KABUPATEN INDRAGIRI HULU TAHUN 2014-2015 - Ria Suci Pertiwi; Auradian Marta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Forest and critical land in Indragiri Hulu very concern that 12.20% of the total area Indragiri Hulu, so that efforts are needed to rehabilitate forests and land as a form of saving the forest from extinction. This study aims to investigate the implementation of forest rehabilitation and inhibiting factors as well as supporting the implementation of forest rehabilitation in the District Forestry Office Peranap by Indragiri Hulu.This study uses qualitative research methods with descriptive research, which can be interpreted as a problem-solving process was investigated by describing the state of the research subjects were based on the facts that appear during the study were then followed by the popularity of existing theories.Rehabilitation of the forest by the Forest Service in the District Peranap still not optimally in the running management of forest rehabilitation in the form of planning, implementation, monitoring and evaluation. There is a limiting factor namely human resources, sanctions, and infrastructure rehabilitation activities. While supporting factors in forest rehabilitation namely the will of society, the potential of good land resources, and the availability of seeds / seedlings.Keywords: Forest Rehabilitation